The equations $x^2−4x+k=0$ and $x^2+kx−4=0$, where $k$ is a real number, have exactly one common root. What is the value of $k$?

I know the answer but can it be done with the relation of roots. $a$ and $b$ are roots of equation 1 and $a$ and $c$ are roots of equation 2. So the relations are :-

  1. $a + b = 4$
  2. $ab = k$
  3. $a + c = (-k)$
  4. $ac= (-4)$

I tried doing all the stuff but couldn't get it. Can we find it using these 4 equations?

  • 2
    $\begingroup$ Hint: subtract the first equation to the second, you will get the expression of the common root $x$ expressed as a function of $k$. $\endgroup$ – Jean Marie Sep 21 '17 at 7:44

Using your equations . . .

  1. $\;a + b = 4$
  2. $\;ab = k$
  3. $\;a + c = (-k)$
  4. $\;ac= (-4)$

Adding equations $(1)$ and $(4)$, we get $$a + b + ac=0\tag{5}$$ Adding equations $(2)$ and $(3)$, we get $$a + c + ab=0\tag{6}$$ Subtracting equation $(6)$ from equation $(5)$, we get \begin{align*} &b-c + ac - ab = 0\\[4pt] \implies\;&b-c+a(c-b) = 0\\[4pt] \implies\;&(b-c)(1-a)= 0\\[4pt] \implies\;&b=c\;\;\text{or}\;\;a=1\\[4pt] \end{align*}

If $b=c$, then the left-hand-sides of equations $(2)$ and $(4)$ are equal, hence the right-hand-sides must also be equal, which yields $k=-4$. But for $k=-4$, the two given equations are identical, hence have two common roots, not one.

Hence we must have $a=1$.

Using $a=1$ in equation $(1)$ yields $b=3$, and then equation $(2)$ yields $k=3$.


If they have the same root, then $$x^2-4x+k=x^2+kx-4$$ That means $$-4x+k=kx-4\to kx+4x=k+4\to x=1$$ Plug this in one of the two equations and get $1-4+k=0\to k=3$

Indeed $x^2-4x+3=0\to x_1=1,\;x_2=3$ and

$x^2+3x-4=0\to x_1=1;\;x_2=-4$

Hope this helps


If $a+b=4$, then $a^2 + ab = 4a$. So

$$a^2-4a+k=0. \tag 1$$

If $a+c=-k$, then $a^2+ac=-ka$. So

$$a^2 + ka -4 = 0. \tag 2$$

So $0 = (a^2 + ka -4)-(a^2-4a+k)=(k+4)a-(k+4)=(k+4)(a-1)$

So $k=-4$ or $a=1$

If $k=-4$, then both trinomials become $x^2-4k-4$ and so they have two roots in common: $2+\sqrt 8$ and $2-\sqrt 8$.

If $a=1$, then plugging $a=1$ into equations $(1)$ and $(2)$ yields the equations

$$1-4+k=0 \qquad \text{and} \qquad 1+k-4=0$$

and both equations have the single solution $k=3$.


Two polynomials have a common root if and only if their resultant vanishes.

The resultant $R(p(x), q(x))$ of two polynomials of degrees $m$ and $n$, respectively, is the determinant of the $(m + n) \times (m + n)$ matrix defined as follows. Write the coefficient of $p(x)$ in the first row followed by $n - 1$ zeros. In the next row the coefficients are displaced one place to the right, with one zero to the left and $n - 2$ zeros to the right. Continue in this fashion until the $nth$ row is $n - 1$ zeros followed by the coefficients of $p(x)$. For the last $m$ rows, we do the same thing with $p(x)$ and $q(x)$ interchanged.

For your case, let $p(x) = x^{2} - 4x + k,\; q(x) = x^{2} + kx - 4$. So the resultant is $$ R(p(x), q(x)) = \mbox{det}\left(\begin{array}{cccc} 1 & -4 & k & 0\\ 0 & 1 & -4 & k\\ 1 & k & -4 & 0\\ 0 & 1 & k & -4\\ \end{array}\right).$$ Computer solution gives $k = 3, k = -4$. So there are two common roots, as quasi mentioned.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.